2020
DOI: 10.1037/mot0000178
|View full text |Cite
|
Sign up to set email alerts
|

A cross-cultural investigation of metamotivational knowledge of construal level in the United States and Japan.

Abstract: Metamotivation refers to the beliefs and mechanisms by which people regulate their motivational states to achieve desired ends. Recent metamotivation research demonstrates that Westerners recognize the benefits of engaging in high-level and low-level construal (i.e., motivational orientations toward abstract, essential vs. concrete, idiosyncratic features) for performance on various tasks. We present the first cross-cultural investigation of this knowledge of how to create such construal level task-motivation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 58 publications
1
10
0
Order By: Relevance
“…This is consistent with previous findings on the cross-cultural consistency on people’s perceived enjoyment during waiting periods (Buttrick et al, 2019), but the current study extended its scope from actual experiences to metacognitive accuracy about just thinking. Our results also join recent emerging findings showing the cross-cultural consistency of metamotivational beliefs on other domains (Murayama et al, 2016; Nguyen et al, 2020). However, one notable observation is that, while we found a consistent relative underestimation effect across Japanese and United Kingdom samples, the Japanese sample showed lower absolute magnitude of ratings than the United Kingdom sample for both predicted and experienced task motivation (see Figures 2–4 and 6 for Japanese sample and Figure 5 for the United Kingdom sample).…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with previous findings on the cross-cultural consistency on people’s perceived enjoyment during waiting periods (Buttrick et al, 2019), but the current study extended its scope from actual experiences to metacognitive accuracy about just thinking. Our results also join recent emerging findings showing the cross-cultural consistency of metamotivational beliefs on other domains (Murayama et al, 2016; Nguyen et al, 2020). However, one notable observation is that, while we found a consistent relative underestimation effect across Japanese and United Kingdom samples, the Japanese sample showed lower absolute magnitude of ratings than the United Kingdom sample for both predicted and experienced task motivation (see Figures 2–4 and 6 for Japanese sample and Figure 5 for the United Kingdom sample).…”
Section: Discussionsupporting
confidence: 91%
“…Beyond regulatory focus, future cross-cultural research should examine people’s beliefs regarding other motivational states. For example, recent research demonstrated that people in the United States and Japan recognize how to create construal-level task-motivation fit (Nguyen et al, 2020). Recent research also found that American and Japanese participants similarly did not recognize that extrinsic incentives can undermine their intrinsic motivation for a task (Murayama et al, 2016), thereby providing insight into people’s misbeliefs.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, Westerners may exhibit a promotion bias, whereas Easterners may have a prevention bias—consistent with cross-cultural research showing that Easterners and Westerners are particularly motivated by the culturally dominant regulatory focus (Lockwood et al, 2005; Uskul et al, 2009; see also Elliot et al, 2001). It is also possible, however, that metamotivational knowledge may operate similarly across cultures (Nguyen et al, 2020), even if those cultures differ in their predominant regulatory focus. Thus, one aim of this work is to examine the role that culture may (or may not) play in shaping a promotion or prevention bias in each culture.…”
Section: Cross-cultural Investigation Of Metamotivational Beliefsmentioning
confidence: 99%
See 2 more Smart Citations